EFEKTIVITAS PELAKSANAAN PROGRAM USAHA EKONOMI SIMPAN PINJAM (UED-SP) CEMERLANG DESA DOMPAS KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Nordianti "; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Poverty is not just about economic issues. The number of poor people led to make Economic growth become slowing. One form of government concern for this problem is to create a program that is Village Empowerment Program (PPD). In PPD, there are several forms of empowerment, one of them is a program of Economic Business Village Savings and Loans (UED-SP) in the form of government provides loans or funding business capital to the society to develop the society business in order to improve the village economy and the society welfare. This study aims to find out the effectiveness of the implementation of Economic Program of Savings and Loans Economic Village (UED-SP) and the factors that influence the Effectiveness of UED-SP Program Implementation in Dompas Village, Bukit Batu Sub-district, Bengkalis Regency.Based on the theory of Mahmudi that to find out the effectiveness of a program based on several indicators namely Input, Process, Output, and Outcome. The research method that is used is descriptive qualitative with purposive sampling technique. The informants in this research are UED-SP Chairman, UED-SP Management Team, and UED-SP Cemerlang Users of Dompas Village.From the results of descriptive qualitative data analysis found that the Effectiveness of UED-SP Program Implementation in Dompas Village, Bukit Batu District, Bengkalis Regency is quite effective. It can be seen from the participation of some society to use the funds from UED-SP as the venture capital, the UED-SP Program continuity and the slightly increased society economy. In this study, it is known that the factors that influence the Effectiveness of UED-SP Program Implementation in Dompas Village, Bukit Batu Subdistrict, Bengkalis District, is less effective or less appropriate fund targets, and lack of human resources coaching for management team or borrower of loan itself.keywords: Effectiveness, Program, Economic Business Village Savings and Loans(UED-SP)